2007
DOI: 10.1002/chem.200601022
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Stability and Guest Affinity of Tris(3‐ureidobenzyl)amine Capsules in Solution

Abstract: In non-competitive solvents, the tris(3-ureidobenzyl)amines 1 a-c form dimeric assemblies in which guests such as CH(3)CN, CH(3)NO(2), CH(2)Cl(2), CH(3)I, CH(2)BrCl, CH(2)Br(2), CHCl(3) and C(6)H(6) can be encapsulated. Variable temperature (1)H and (1)H,(1)H-ROESY NMR spectroscopy, as well as pulsed-gradient spin-echo (PGSE) diffusion measurements were used to investigate the encapsulation within 1 a1 a (1 a: tris{3-[N'-(4-butylphenyl)ureido]benzyl}amine). Kinetic parameters for the encapsulation of CH(3)NO(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…Previously, we demonstrated that dimeric aggregates 2·2 are excellent containers for MeI, CH 2 Cl 2 and MeNO 2 . [22] At À15 8C, the (Figure 8, left), which indicates that the presence of these guests inside the cavity may not influence the regioselectivity of the self-assembly process. [27] Interestingly, the spectra reveal two different resonances for MeI and MeNO 2 inside 5 a·5 a, with slightly different chemical shifts in a 2:1 ratio (Figure 8 a and 8 c, right).…”
Section: F{mentioning
confidence: 94%
See 3 more Smart Citations
“…Previously, we demonstrated that dimeric aggregates 2·2 are excellent containers for MeI, CH 2 Cl 2 and MeNO 2 . [22] At À15 8C, the (Figure 8, left), which indicates that the presence of these guests inside the cavity may not influence the regioselectivity of the self-assembly process. [27] Interestingly, the spectra reveal two different resonances for MeI and MeNO 2 inside 5 a·5 a, with slightly different chemical shifts in a 2:1 ratio (Figure 8 a and 8 c, right).…”
Section: F{mentioning
confidence: 94%
“…Whereas the spectrum of 5 c is too complex to extract any conclusion, the 1 H NMR spectra of 5 a-b show typical signatures of tribenzylamine-derived capsules ( Figure 6). [21,22] Large shifts to lower frequencies were observed for the signals of the protons of the pendant aromatic substituents as well as the protons located at the C2 position of the tribenzylamine skeleton (labelled in Scheme 2), the latter shifted as much as 2 ppm to lower frequencies. Thus, whereas protons at C2 resonate at 7.5 ppm in [D 6 ]DMSO, they appear as broad signals at 5.7-5.9 ppm in the halogenated solvent.…”
Section: F{mentioning
confidence: 95%
See 2 more Smart Citations
“…to give clathrates -opens the door to specific interactions with neutral molecules in the field of molecular recognition, or host-guest chemistry [33][34][35]. Moreover, aromatic urea derivatives have shown the ability to form oligomeric assemblies, or capsules, in which guests can be encapsulated in solution, and the complex capsules persist even in the solid state, as demonstrated by X-ray analysis [36][37][38]. solution.…”
mentioning
confidence: 99%